Lifelong Learning in Public Community Culture in Hungary - Gyányi István; Juhász Erika (Acta Educationis Generalis)
The importance of non-formal and informal learning is gaining increasing prominence in academic research (Chernenko, 2023; Corrales-Herrero & Rodríguez-Padro, 2018; Juhász, 2018). This study explores the appearance of lifelong learning (LLL) in the legal framework of Hungary's cultural sector, examining how various pieces of legislation interact to regulate the field.